Vibron-assisted spin excitation in a magnetically anisotropic molecule - N. Bachellier (Nature Portfolio, 2020)
Electrically manipulating molecular magnetism is a challenge to overcome for applications in high-density storage. Here, the authors use inelastic electron tunneling spectroscopy to show that a vibron-assisted spin excitation in a nickel-nickelocene complex exceeds a pure spin excitation in energy and amplitude.